PENINGKATAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS IV MELALUI MODEL RECIPROCAL TEACHING - Sundahry Dahry; Yogi Irdes Putra (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The purpose of this study is to describe the improvement of the fourth grade student learning outcomes through the reciprocal teaching model at SD 19 Sungai Talang Tarusan. This type of research is a classroom action research with a subject of 28 students. This research was conducted in the even semester of the 2015/2016 academic year. The research instrument used was the teacher's activity observation sheet and the student's cognitive learning outcome test sheet. The implementation of science learning through the reciprocal teaching model of class IV went well. Based on the research results, the learning outcomes of the cognitive domain level of knowledge in the first cycle had an average value of 78.2 and in the second cycle the average value was 87.6. The increase in the cognitive domain of knowledge from cycle I to cycle II with the difference in mean value was 9.4. While the cognitive learning outcomes of the level of understanding in the first cycle an average value of 69.1 and in the second cycle an average value of 84.3. The increase in cognitive understanding from cycle I to II the average value was 15.2. This means that teaching science through the reciprocal teaching model can improve the learning outcomes of fourth grade students at SD 19 Sungai Talang and it can be concluded that the reciprocal teaching model can improve student learning outcomes..